2017
DOI: 10.1097/dbp.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Among Adolescents with Attention-Deficit/Hyperactivity Disorder: Reasons for Use, Knowledge of Risks, and Provider Messaging/Education

Abstract: Objective Adolescents with ADHD are at increased risk for alcohol and marijuana use. This study’s objective is to describe adolescents’ ADHD-specific reasons for marijuana use, knowledge of ADHD-specific alcohol risks, and reported subspecialty provider messaging/education regarding alcohol use among adolescents with ADHD. Methods Youths with ADHD ages 12–18 years completed a survey about alcohol and marijuana use, ADHD-specific reasons for marijuana use, knowledge of ADHD-specific alcohol risks, and reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…53 Similarly, adolescents with ADHD who use cannabis have often reported thinking that it would lead to improvement in their ADHD symptoms. 54 These observations are in line with globally increasing trends in adolescent cannabis use in the face of decreased use of other illicit substances. 55 Together with other factors, such as tetrahydrocannabinol (THC) potency roughly tripling from 1995 to 2014, 56 it is increasingly critical to establish the links between ADHD and cannabis use and their shared impact on neurodevelopmental outcomes.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…53 Similarly, adolescents with ADHD who use cannabis have often reported thinking that it would lead to improvement in their ADHD symptoms. 54 These observations are in line with globally increasing trends in adolescent cannabis use in the face of decreased use of other illicit substances. 55 Together with other factors, such as tetrahydrocannabinol (THC) potency roughly tripling from 1995 to 2014, 56 it is increasingly critical to establish the links between ADHD and cannabis use and their shared impact on neurodevelopmental outcomes.…”
Section: Introductionsupporting
confidence: 55%
“…By contrast, high school seniors do not perceive cannabis to be particularly risky, with only 26.7% reporting use as harmful 53 . Similarly, adolescents with ADHD who use cannabis have often reported thinking that it would lead to improvement in their ADHD symptoms 54 . These observations are in line with globally increasing trends in adolescent cannabis use in the face of decreased use of other illicit substances 55 .…”
Section: Introductionmentioning
confidence: 63%
“…We have previously reported that youth who report having been asked about whether they use alcohol were more likely to have also received advice or counseling regarding alcohol [10], thus failure to screen in subspecialty care may represent a missed opportunity. Accurate information from a healthcare provider may take particular importance as parents of children with chronic medical conditions may not be aware of the unique vulnerabilities of their children [17].…”
Section: Discussionmentioning
confidence: 99%